Laju Pertumbuhan Lamun Enhalus acoroides yang Di Transplantasi dengan Menggunakan Metode Terfs Di Perairan Pantai Desa Waai Kabupaten Maluku Tengah - T, Rosmawati; Huliselan, N. V; Khouw, A. S.; Tupan, Ch. I. (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
Coastal utilization that is not directed by the surrounding community such as sand and stone extraction and disposal of solid and liquid waste to the beach can cause damage to coastal ecosystems including seagrass ecosystems. Efforts to restore the diminishing condition of the seagrass ecosystem is through seagrass transplantation activities using the TERFS (Transplanting Eelgrass Remotely With Frame System) method. This research was conducted from February 2019 - 31 May 2019. This study aimed to analyze the survival rate and growth rate and physical chemical factors of the waters that affect the growth of the seagrass Enhalus acorides transplanted using the poly bag method and the TERFS method (Transplanting Eelgrass Remotely With Frame System) in the coastal waters of Waai Village, Central Maluku Regency. The results showed that the Enhalus acorides seagrass had a survival rate of 100%. The value of the growth of seagrass for three weeks of observation is in frame 1 of 0.43 cm / day, in frame II of 0.47 cm / day and in frame III of 0.46 cm / day. The average value of the physical chemistry parameters of the waters at the transplantation location using the coastal waters of Waai Village, Central Maluku Regency is still within the range of environmental parameters of the marine waters supporting the growth of seagrass Enhalus acorides, including temperatures of 30.67 ℃, brightness of 100%, water depth of 45.67 cm, current velocity of 0.46 cm / sec, salinity of 29 ‰ and water pH of 7.53. The average value of nitrate content in the water column